Factors that influence students’ writing skill from the fifth academic year in the English III course in groups 02 and 03 of the International affairs major at the school of Jurisprudence and Social Sciences from the University of El Salvador, semester I 2018 - Pérez Monge, José Luis
Writing is a very important and fundamental language skill for all kinds of purposes, but especially when writing an academic paper. Therefore, the present research project aims to find out the factors that influence students’ writing skill from the fifth academic year in the English III course in groups 02 and 03 of the International Affairs Major at the School of Jurisprudence and Social Sciences from the University of El Salvador, semester I – 2018. This report lists the factors that are affecting the students’ writing skill as well as the most common issues found in their academic papers. One of the most important things to remember when teaching writing is that writing is a process, therefore, teaching how to write effectively is one of the most important life-long skills educators impart to their students. Important information can be found in the theoretical framework, information that reinforces the research. Among some of the information can be mentioned: different approaches to the teaching of writing, the most common factors students face when learning to write academic papers, and the like. This project also explains the process followed by the research team to collect meaningful and important information regarding the factors that affect students’ writing skill as well as the most common issues identified in their academic papers. For carrying out this present study, the research questions were answered by analyzing the information gathered through the surveys applied to both students and teachers and also by means of checking students’ academic papers using a check list which contained important aspects of writing which should be taken into account when writing academic papers. At the end, conclusions are presented based on the main findings and recommendations for students, teachers and the Jurisprudence and Social Science school are given with the intention of improving the students’ writing skill so they can be more prepared when facing the labor market.